The Influence of Working Capital on Income of Food Traders MSMEs in Sukaharja, Karawang - Prasetyo, Kukuh Wahyu; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to determine the partial effect of working capital on income in MSMEs Food Traders in Sukaharja Karawang. This research was conducted using quantitative methods with descriptive and verification approaches, with the sampling technique being simple random sampling. The population in this study were 103 food MSME players and a sample of 51 food MSME players. In this study, the data collection technique used was a questionnaire distributed to food trader MSME players in Sukaharja Karawang. The analysis model used is simple linear regression analysis. Based on the results of hypothesis testing, it shows that the value of tcount ≥ ttabel (3.232> 2.010), it can be said that there is a significant influence between working capital and income in food trader MSMEs in Sukaharja Karawang.